PERBEDAAN STRUKTUR ANATOMI TUMBUHAN PENGHASIL GAHARU Aquilaria spp. DAN Gyrinops versteegii - Widoyanti, -; Prasetyorini, -; Ismanto, - (-)
The cross and longitudinal section anatomical structure of Aquilaria malaccensis, A. beccariana, A. decipiens, A. microcarpa and Gyrinops versteegii has been studied using paraffin method following Sass (1951) as well as paraderm section and maceration as described in Cutler (1978). The results showed that there were differences in the type of crystal, the number of neighboring cells, the epidermal cells form on upper and lower leaf surfaces and in stomatal index. Further more the differences were also appeared at fingers pith and niche forms. The stomatal index percentage was different significantly with the highest percentage found in A. decipiens 8.47%, followed by A. beccariana 6.73%; A. microcarpa 3.84%; A. malaccensis 3.49% and the lowest percentage was G. versteegiiie 1.60%. Key words: Aquilaria spp., Gyrinops versteegii, plant anatomy, stomatal index